2018
DOI: 10.1186/s12864-018-4591-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles of bovine monocyte-derived macrophages infected in vitro with two strains of Streptococcus agalactiae

Abstract: BackgroundMicroRNAs (miRNAs) are short, non-coding RNAs that regulate gene expression at the post-transcriptional level and play a key role in the control of innate and adaptive immune responses. For a subclinical infection such as bovine streptococcal mastitis, early detection is a great challenge, and miRNA profiling could potentially assist in the diagnosis and contribute to the understanding of the pathogenicity and defense mechanisms. We have examined the miRNA repertoire and the transcript level of six k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Red denotes gene nodes that were increased in expression, and green denotes nodes that were decreased in expression in SMD samples than HMD samples. The red circle denotes a commonly shared node in the three comparisons in vitro with S. agalactiae [48]. The protein encoded by IL26 is a member of the IL10 family of cytokines [49], which has been shown to exhibit anti-bacterial activity against a wide range of bacteria including S. aureus [50], suggesting a broader role in host defenses against bacteria [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red denotes gene nodes that were increased in expression, and green denotes nodes that were decreased in expression in SMD samples than HMD samples. The red circle denotes a commonly shared node in the three comparisons in vitro with S. agalactiae [48]. The protein encoded by IL26 is a member of the IL10 family of cytokines [49], which has been shown to exhibit anti-bacterial activity against a wide range of bacteria including S. aureus [50], suggesting a broader role in host defenses against bacteria [51].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sequence variation at IFNL3 has been shown to be associated with hepatitis B virus (HBV) infection in a Chinese human population [ 47 ]. CCL26 encodes a secreted protein involved in immunoregulatory and inflammatory processes, which Anna et al observed to be associated with IL4-mediated signaling pathways in bovine macrophages challenged in vitro with S. agalactiae [ 48 ]. The protein encoded by IL26 is a member of the IL10 family of cytokines [ 49 ], which has been shown to exhibit anti-bacterial activity against a wide range of bacteria including S. aureus [ 50 ], suggesting a broader role in host defenses against bacteria [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell components of milk were largely removed from our milk samples; however, the somatic cells present in milk, including 75% white blood cells and 25% epithelial cells, are increased during mastitis . Aberrant small RNA expression between normal and mastitis milk may be derived from somatic cells and exosomes . miR‐10a, miR‐146a, miR‐146b, miR‐221, and miR‐223 are associated with the regulation of innate immunity and mammary epithelial cell function in tissues challenged with Streptococcus uberis .…”
Section: Discussionmentioning
confidence: 99%
“…Other differentially expressed miRNAs, bta-miR-92b, bta-miR-1343-3p and bta-miR-1306 were down-regulated in our study. A previous study observed that their down-regulation in bovine monocyte-derived macrophages being challenged with Streptococcus agalactiae [27]. The results suggest that bta-miR-92b, bta-miR-1343-3p and bta-miR-1306 may play a role in MDMs after bacterial infection and could be used as a candidate for further research.…”
Section: Discussionmentioning
confidence: 79%
“…Li Jizong et al performed high-throughput sequencing to analyze small RNA libraries of CPIV3-infected and mock-infected MDBK cells, and 249 known and 152 novel miRNAs were differentially expressed in MDBK cells after CPIV3 infection [26]. Lewandowska-Sabat et al identified the Streptococcus agalactiae -induced differential regulation of miRNAs in bovine macrophages, and the predicted target genes were significantly enriched in interleukin-4-mediated signaling events and the intrinsic pathway for apoptosis [27]. In the study of miRNA expression profile responses to Streptococcus uberis in vivo, Lawless et al profiled the miRNA expression in both milk and blood monocytes, and 26 miRNAs and more than 3500 genes were identified as being significantly differentially expressed over 48 h. Pathway analysis revealed that the predicted target genes of down-regulated miRNAs were highly enriched in terms of innate immunity [28].…”
Section: Introductionmentioning
confidence: 99%